2023
DOI: 10.1530/ec-22-0461
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune-inflammation index is associated with decreased bone mass density and osteoporosis in postmenopausal women but not in premenopausal women

Abstract: Purpose: This study aims to investigate the associations of the systemic immune-inflammation index (SII) with bone mineral density (BMD) and osteoporosis in adult females from a nationally representative sample. Methods: A cross-sectional study was performed among 4,092 females aged ≥20 years from the National Health and Nutrition Examination Survey (NHANES) 2007–2010. Linear and logistic regressions were applied to explore the relationships of SII with BMD and the risk of osteoporosis, respectively. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…SII can be calculated through a routine blood examination, and it has the advantages of being fast, efficient, simple, and low in cost. Previous studies have confirmed that the SII has good clinical application value in the diagnosis of chronic diseases such as tumours, cardiovascular diseases, osteoporosis, and rheumatoid arthritis 26 29 . Research suggests that chronic low-grade inflammation associated with ageing may be an important cause of sarcopenia 30 .…”
Section: Introductionmentioning
confidence: 79%
“…SII can be calculated through a routine blood examination, and it has the advantages of being fast, efficient, simple, and low in cost. Previous studies have confirmed that the SII has good clinical application value in the diagnosis of chronic diseases such as tumours, cardiovascular diseases, osteoporosis, and rheumatoid arthritis 26 29 . Research suggests that chronic low-grade inflammation associated with ageing may be an important cause of sarcopenia 30 .…”
Section: Introductionmentioning
confidence: 79%
“…Therefore, osteoclasts are sensitive to TNF-α, whereas RANKL is involved in maintaining dendritic cell survival and immune system functioning ( 10 , 11 ). Prolonged changes in the cytokine profile alter the functioning of many cells outside the immune system, especially osteoclasts ( 12 ). Effector T-cells, especially Th-17 cells produce IL-17 that play a crucial role in osteoclast activation.…”
Section: The Role Of the Immune System In The Pathogenesis Of Bone Di...mentioning
confidence: 99%
“…Systemic immune-inflammation index (SII), a new inflammatory biomarker based on platelet count × Neutrophil count/lymphocyte count calculation 7 , 8 , was proved to reflect the degree of systemic inflammation 9 . It reported that SII is independently associated with multisystem diseases, such as cardiovascular disease 10 , diabetic nephropathy 11 , rheumatic immune disease 12 , 13 , cancer 14 16 , osteoporosis 17 , metabolic diseases 18 . Different from traditional inflammatory factor, blood routine examination is convenient and inexpensive, and has higher practicability in disease research.…”
Section: Introductionmentioning
confidence: 99%